Coaching youth gymnastics: An essential guide for coaches, parents and teachers - Readhead, L. (Crowood, 2016)
Coaching Youth Gymnastics is an invaluable resource for both new coaches and also for more experienced teachers. Those who train coaches will also find much of value in the book. The various disciplines of gymnastics are explained, together with how they fit into the framework of international gymnastic competition, and the author discusses various coaching styles and how they might best be applied in different circumstances. Topics covered in this new book include the role of the coach; sports psychology; floor exercise skills; coaching use of apparatus and preparing for competition. The role of the coach, Sports psychology, floor exercise skills, coaching use of apparatus, preparing for competition.